SOSIALISASI DAN PELATIHAN PANGAN ORGANIK BAGI MASYARAKAT UMAT PAROKI SANTO YOSEF KEDIRI KEUSKUPAN SURABAYA - Trihastuti, Dian; Jaka Mulyana, Ignasius; Gunawan, Ivan; Permata Sari Hartanti, Lusia (Jurnal Abdimas Musi Charitas, 2022)
Organic food is the product of organic farming. Organic farming is an agricultural cultivation technique that uses natural (local) materials that emphasizes the protection of biotic and abiotic properties in the environment. The organic farming methods apply the principle of zero chemical synthetic, that is, without the use of artificial chemicals such as fertilizers and pesticides. The organic farming aims to provide food and agricultural products that are safe for public health and do not damage the environment. The challenges faced in developing organic agriculture are low productivity, distribution of production results, the number and expertise of human labor, the presence of plant-disturbing organisms, and the lack of public understanding of organic food. This Community Service aims to increase understanding and awareness of the importance of organic farming. In addition, the material also includes the supply chain of organic foods. The evaluation survey shows that 43% participant agree that the program is useful to increase their understanding about organic farming. The average participant satisfaction toward the program execution is 3,4 out of 4 scale. The participants are Orang Muda Katolik (OMK) from Paroki St. Vincentius A Paulo Kediri, St. Yosef Kediri and St. Markus Pare Keuskupan Surabaya.